2007
DOI: 10.1634/stemcells.2007-0275
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Granulocyte Colony-Stimulating Factor After Myocardial Infarction Enhances the Recruitment of Hematopoietic Stem Cell-Derived Myofibroblasts and Contributes to Cardiac Repair

Abstract: The administration of granulocyte colony-stimulating factor (G-CSF) after myocardial infarction (MI) improves cardiac function and survival rates in mice. It was also reported recently that bone marrow (BM)-derived c-kit؉ cells or macrophages in the infarcted heart are associated with improvement of cardiac remodeling and function. These observations prompted us to examine whether BM-derived hematopoietic cells mobilized by G-CSF administration after MI play a beneficial role in the infarct region. A single he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 25 publications
2
48
0
Order By: Relevance
“…Fsp1 but not α-smooth muscle actin was found in non-myocyte cells from hypertrophic hearts ( Figure 1C). Activated non-myocyte cells may also be derived from circulating cells (14,(46)(47)(48). Alternatively, the enhanced biomechanical forces resulting from sarcomere protein mutations (7,8) could also provide a local mechanism for activating resident non-myocyte cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fsp1 but not α-smooth muscle actin was found in non-myocyte cells from hypertrophic hearts ( Figure 1C). Activated non-myocyte cells may also be derived from circulating cells (14,(46)(47)(48). Alternatively, the enhanced biomechanical forces resulting from sarcomere protein mutations (7,8) could also provide a local mechanism for activating resident non-myocyte cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that smooth muscle progenitor cells derived from bone marrow participate in neointimal formation after allotransplantation, post-angioplasty restenosis, and hyperlipidemia-induced atherosclerosis 33) . A recent study demonstrated that G-CSF treatment increased the mobilization of hematopoietic stem cell-derived myofibroblasts in the infarcted heart and enhanced cardiac repair in a mouse AMI model 34) . Increased accumulation of smooth muscle cells in the plaque by G-CSF treatment may result from increased mobilization of hematopoietic stem cell-derived myofibroblasts from bone marrow.…”
Section: Gh Gm3mentioning
confidence: 99%
“…22 We found that many hematopoietic stem cell-derived cells, which have a fibroblast-like elongated morphology, are retained at the infarcted myocardium at 7 days post-MI. These cells (A-D) Epicardial and endocardial layer of the infarced area was separately shown in the control and G-CSF treated groups.…”
Section: Discussionmentioning
confidence: 67%